Ferramentas da logística na redução de estoques: um estudo de caso - Veiga, Ricardo Kozoroski (2003)
The strong competitiveness and the narrow diference between productives process caused by easy access to information, machines and process, have been taking us to the sdudy and development of Logistic and Suply Chain Management. A little explored and many times considered as secondly important, the Logistic have been demonstrating the main competitive differential in the organizations of the future. Being Logistic the process of strategic management to buy, move and storage material, and motivated by the innovations of this kind of management, was used the case of Comil Buses, situated in Erechim, RS, to produce this work that intends to present the tools useds to manager and a new tool developed to reduce stocks and to improve the competitivity of the companies in the market. About stocks management, that can be described as the management of programming and storage of parts in a rational and economic way, will be shown an algorithm, the base of the the program named of EXTOCK. This new tool will give suport to an effective programming, made to do a safety reduction of the stock costs of bought items. Based on the evaluation of supplier, structure of the product, cost and the transport company, this program can be used in any stage of programming, to new or old items. With the EX-TOCK in test, will be possible to show the evolution of stock values, and the positive or negatives points of that program.